ANAKKU ENURESIS (Sebuah Studi Fenomenologi) - Esya Asmanda (Jurnal Riset Psikologi, 2018)
Abtrack: My child’s got enuresis (a phenomenological study). Enuresis is an incident of bedwetting at an age where a child should have stopped bedwettin. It can cause stress for parents and children. This study aims to understand parents perceptions regarding the enuresis of their children. The study uses qualitative phenomenological method using the IPA (Interpretative Phenomenological Analysis) technique. The subjects are four people who are suitable with the study based on purposive sampling method. This study uses interview and observation techniques. The results of the study showed that the positive perception of parents that was shown by the positive tendency of parents to take care for their children. Based on this study, researcher found 13 themes related to parents' perceptions of enuresis, namely knowledge of the layman, treatment of facing enuresis, psychological impact of parents, positive thoughts, history of enuresis in the family, role of the family, cooperation with partners, partner support, the thought of enuresis as usual case, attempts to treat enuresis, perception after seeing a doctor and treatment after seeing a doctor.Keyword : Perception, parents, child with enuresis. Abstrak: Anakku enuresis (sebuah studi fenomenologi). Enuresis adalah kejadian mengompol pada usia yang tidak sewajarnya dan hal ini dapat meninmbulkan stres bagi orang tua dan anak. Penelitian ini bertujuan untuk memahami persepsi orang tua terkait enuresis anaknya. Penelitian ini menggunakan metode kualitatif fenomenologi dengan menggunakan teknik IPA (Interpretative Phenomenological Analysis). Subjek penelitian ini berjumlah 4 orang yang didapat dengan metode purposive sampling yang dianggap cocok dengan penelitian ini. Penelitian ini menggunakan teknik wawancara dan observasi. Hasil penelitian menunjukkan persepsi positif orang tua yang ditunjukkan dengan kecenderungan positif perilaku orang tua merawat anak. Berdasarkan penelitian ini, peneliti menemukan 13 tema terkait persepsi orang tua pada enuresis, yakni pengetahuan awam, perlakuan menghadapi enuresis, dampak psikologis orang tua, pikiran positif, riwayat enuresis dalam keluarga, peran pihak keluarga, kerjasama dengan pasangan, dukungan pasangan, enuresis sebagai hal biasa, usaha mengobati enuresis, persepsi setelah ke dokter dan perlakuan setelah ke dokter.Kata Kunci :Persepsi, orang tua, anak enuresis.